2008
DOI: 10.1021/om800635d
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Amidation of 9-Iodo-m-carborane and 2-Iodo-p-carborane at a Boron Atom

Abstract: The palladium-catalyzed amidation of B-iodocarboranes by various amides is described for the first time. The reactions of 2-iodo-1,12-dicarba-closo-dodecaborane (2-iodo-p-carborane) with acetamide, 2-pyrrolidinone, caprolactam, p-methylbenzamide, and 2-phenylacetamide using the system Pd(dba)2/BINAP/NaH (dba = dibenzylideneacetone; BINAP = rac-2,2′-bis(diphenylphosphino)-1,1′-binaphthyl) in dioxane at 100 °C gave 2-p-carboranyl derivatives of these amides in good to high yields. Similar reactions of 9-iodo-1,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Phosphine ligands such as dppb, DIPPF, BINAP, and XantPhos were found to facilitate a variety of B-N, B-O, and B-P bond forming reactions. 37,87,88,90,92,95 Notably, these works feature a broader catalyst screen which showed that electron-rich ligands such as dialkyl biaryl phosphines, PCy 3 , P t Bu 3 , and IMes have some activity towards B-N and B-O bond formation. 87 Furthermore, we demonstrated that, with an appropriately electron-rich ligand, B-bromo-carboranes can be excellent cross-coupling substrates.…”
Section: Mechanistic Considerations Of Metal-catalyzed Polyhedral Bor...mentioning
confidence: 99%
“…Phosphine ligands such as dppb, DIPPF, BINAP, and XantPhos were found to facilitate a variety of B-N, B-O, and B-P bond forming reactions. 37,87,88,90,92,95 Notably, these works feature a broader catalyst screen which showed that electron-rich ligands such as dialkyl biaryl phosphines, PCy 3 , P t Bu 3 , and IMes have some activity towards B-N and B-O bond formation. 87 Furthermore, we demonstrated that, with an appropriately electron-rich ligand, B-bromo-carboranes can be excellent cross-coupling substrates.…”
Section: Mechanistic Considerations Of Metal-catalyzed Polyhedral Bor...mentioning
confidence: 99%
“…Similar to the functionalization of aromatic hydrocarbons, an obvious choice of methods for installing functional groups on boron vertices would involve metal‐catalyzed cross‐coupling. Early work by Zakharkin, followed by Jones, Hawthorne, Viñas, and Beletskaya and Bregadze has shown that the cross‐coupling with boron‐functionalized 9‐B‐iodocarborane coupling partners ( III and IV , Figure ) can be a powerful method for installing functional groups at the boron vertices . Oxidative addition of 9‐B‐iodocarborane to form a M−B bond is a critical step in the cross‐coupling cycle, and isolating this key intermediate could shed light on strategies to further develop this chemistry.…”
Section: Figurementioning
confidence: 99%
“…34 The catalytic amidination of 9-iodo-m-carborane and 2-iodo-p-carborane have been reported, along with a series of B-substituted acetamide compounds for potential utility in boron neutron capture therapy. 35 The 1:2 adduct of 1-bromo-ortho-carborane and pyridine (3) has been structurally characterised and identified as a significant intermediate in the deboronation of ortho-carborane to a nido-anion. 43 The reduction and subsequent oxidation of meta-carboranes containing bulky groups 1,7-(CR 2 Fc) 2 -1,7-closo-C 2 B 10 H 10 (Fc = (Z 5 -C 5 H 4 )Fe(Z 5 -C 5 H 5 )) (R = methyl or pentamethylene) attached to the cage C atoms affords sterically-crowded ortho-carboranes with unprecedentedly long C-C connectivities.…”
Section: Metallaboranes Including Boron Hydrides and Related Complexesmentioning
confidence: 99%